CONSIDERAÇÕES ACERCA DO CONSUMO DE BEBIDAS ALCOÓLICAS NO BRASIL E NO MUNDO E OS IMPACTOS NA SAÚDE HUMANA (REMUNOM, 2024)
The use of the selected drinks is presente at diferente times in human history, in contexts with social, political, economic and religious relevance. As it is a psychoactive substance, it is extremely consumed, both because it is considered legal and because of the effects and symbolism it assumes, as it is commonly used in celebrations and favors interaction and socialization. The World Health Organization (WHO) debates that the effects of alcohol use on specific and acute health problems are mainly specific to two diferente but related dimensions of consumption: (1) the total volume consumed; (2) the consumption pattern. These two variables, together with individual and social aspects, are related to the magnitude of alcohol-related problems in populations. WHO studies estimate that more than 237 million men and 46 million women around the world suffer from disorders related to the use of this substance. Therefore, it is necessary to implement public policies with the aim of reducing the harm associated with alcohol abuse.